2016
DOI: 10.1080/20426445.2015.1131918
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of recycled fibres with urea-formaldehyde resins

Abstract: The work aimed to study the influence of replacing virgin wood fibres by recycled fibres, made from recovered medium-density fibreboards (MDF) by thermo-mechanical pulping, on the physical-mechanical properties and formaldehyde release of urea-formaldehyde (UF)-bonded MDF. It was found that replacement of 33% virgin fibres by recycled fibres decreased significantly the thickness swelling and water absorption of the UF-bonded MDF and mitigated the formaldehyde release. However, supplanting 33% of virgin fibres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
0
14
1
1
Order By: Relevance
“…Lately, there has been a growing interest in utilizing oligosaccharides in different applications such as biodegradable oxygen barrier films [38][39][40], emulsifiers [41][42][43][44][45][46][47], thermoplastics [48], hydrogels [49], coatings, or adhesives [50]. The remaining fibrous fraction, on the other hand, might be suitable for production of new fiberboards [51][52][53][54][55][56][57], cellulose nanocrystals [58,59], bioethanol [60,61], biogas, and bio-oil using pyrolysis [62,63]; however, utilization as reinforcement and filler material in wood-plastic compounds (WPCs) [64][65][66] and particleboards [67] has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there has been a growing interest in utilizing oligosaccharides in different applications such as biodegradable oxygen barrier films [38][39][40], emulsifiers [41][42][43][44][45][46][47], thermoplastics [48], hydrogels [49], coatings, or adhesives [50]. The remaining fibrous fraction, on the other hand, might be suitable for production of new fiberboards [51][52][53][54][55][56][57], cellulose nanocrystals [58,59], bioethanol [60,61], biogas, and bio-oil using pyrolysis [62,63]; however, utilization as reinforcement and filler material in wood-plastic compounds (WPCs) [64][65][66] and particleboards [67] has also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It revealed that a combination of steam explosion, chemical impregnation, and hammer milling process could be applied to isolate the recycled fibers (Wan et al 2014). However, the recycled fibers still contain cured UF resin and release a high formaldehyde emission from the re-manufactured panel (Roffael et al 2016). Moreover, it has been reported that replacement virgin fibers by recycled fibers over 20% reduced the internal bond strength of the MDF panel (Lubis et al 2018a).…”
Section: Properties Of Recycled Fibersmentioning
confidence: 99%
“…A lot of fines chips are generated during the disintegration process. Moreover, the recycled chips still contain the residues of the cured resin and exhibit a high formaldehyde emission from the re-manufactured panel (Roffael et al 2016). A combination of mechanical and hydrothermal disintegration can reduce the amount of cured resin in the recycled chips.…”
Section: Properties Of Recycled Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The reuse of the separated waste MDF fibers in production of new MDF is the most apparent possible recycling pathway. However, due to a combination of effects such as fiber shortening, changes in the chemical compositions of the fibers and resin residues found on their surface, a deterioration of the mechanical properties in comparison with MDF made from fresh wood can be observed when using hydrothermal or steam-based fractionation processes [19][20][21][22][23][24]. Recently, Moezzipour et al [25] have reported that such negative effects on the fibers can be reduced using electrical heating instead of hydrothermal treatments, leading to improved mechanical properties of the newly produced MDF.…”
Section: Introductionmentioning
confidence: 99%